Synthesis, Radiochemical Purity Control and Stability of Scandium-46-1,4,7-triazacyclononane-1,4,7-triacetic acid (46Sc-NOTA) - Duyeh Setiawan; Iwan Hastiawan; Asri Nurul Bashiroh (Universitas Gadjah Mada, 2018)
Radiotherapy is one of healing method of cancer using radionuclide elements. The radionuclide scandium-46 (46Sc) has a half-life of 83.8 days, beta emission 0.35 MeV and gamma emission 899 and 1120 keV is suitable for studying the chemical aspects, synthesis and stability of scandium complex for radiotherapy. The purposes of this research are synthesis of scandium-46-1,4,7-triazacyclononane-1,4,7-triacetic acid (46Sc-NOTA) labeled compound based on formation of a complex bonding in stoichiometry between radioisotope 46Sc and 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) ligand, and radiochemical purity and stability assay of 46Sc-NOTA. In this research, conducted that optimum moles several variables, namely moles comparison and pH effect was used. The result are optimum conclusion of mole comparison between radioisotope and ligand was 1:2 (46Sc : NOTA) and environment at pH 5. The radiochemical purity and stability assay of 46Sc-NOTA was carried out by paper chromatography and the result showed that 46Sc-NOTA has radiochemical purity of 99.09 ± 0.2% and remained stable for 9 days.